A rotating ring disk electrode study of the oxygen reduction reaction in lithium containing non aqueous electrolyte - Calvo, Ernesto Julio (2013)
We show the effect of a very small addition of LiClO4 to tetraethyl ammonium perchlorate (TEAP) in acetonitrile on the electro-reduction of molecular oxygen (ORR) at a rotating ring (Pt) glassy carbon (GC) disk electrode. While TEA+ cations stabilize the first electron reduction product in acetonitrile, superoxide O2 −, in the absence of Li+ the ORR proceeds by two one-electron sequential steps to the stabilized peroxide. Addition of 10 μM LiClO4 (b1:800 Li+ to TEA+ ratio) strongly affects the ORR mechanism: Both disk (ID) and ring (IR) currents strongly decrease, with less than 0.5% O2 − produced at the GC disk reaching the ring electrode, but still IR follows the same potential dependence as ID. On the other hand, addition of DMSO to acetonitrile 0.1 M LiClO4 stabilizes soluble O2 − detected at the ring since DMSO preferentially solvates Li+ preventing disproportionation of LiO2 into O2 and passivating Li2O2.